Exploring the Relationship between Women’s Travel Behaviour and Adoption of Sustainable Transportation Practices - Ademiluyi, Victoria Oluwatoyin (NIU Journal of Social Sciences, 2024)
The fast and increasingly urban growth necessitated the drastic change in characteristics of travel behaviour of women. Amidst risks involved in different transportation systems and the realities of fiscal constraints, women struggle to have safe access and affordable transportation options. This study examines the relationship between women travels behaviour and adoption of sustainable transportation practices with special references to four (4) urban centres in Ogun State, Nigeria. A total of one thousand three hundred and sixty-six (1,366) completed questionnaires were used for the analysis. Pearson Product Moment Correlation (PPMC) was employed to investigate the correlation between the travel patterns of female’s individuals and the implementation of sustainable transportation methods. The results from the correlation analysis depict a significant relationship between women’s travel behaviour and adoption of sustainable transportation practices in Ogun State. The result further shows that the level of adoption of sustainable, transportation practices significantly influence women’s travel behaviour and the out-of-town trips for all purposes. Keywords: Gender mobility, sustainable transportation, urban growth, travel patterns